Environmental, Social, and Governance (ESG) Profiles, Stock Returns, and Financial Policy: Australian Evidence - Limkriangkrai, M.; Koh, S.; Durand, Robert (Wiley-Blackwell Publishing Asia, 2016)
This study investigates the independent effects of environmental (E), social (S), corporate governance (G), and the composite ESG ratings on stock returns and corporate financing decisions of the largest stocks in the Australian equity market. Firms with high composite ESG ratings tend to increase their leverage. For the individual ratings, we find different inferences: firms with low E and high G ratings tend to raise less debt. Firms with high G ratings hold less cash, while those with low G ratings have lower dividend payouts. S ratings have no impact on corporate financing decisions. There appears to be no significant difference in risk-adjusted returns for portfolios based on ESG ratings, effectively indicating that there is no cost of ESG investment.